2021
DOI: 10.1017/s1473550420000397
|View full text |Cite
|
Sign up to set email alerts
|

Biological safety in the context of backward planetary protection and Mars Sample Return: conclusions from the Sterilization Working Group

Abstract: The National Aeronautics and Space Administration (NASA) and the European Space Agency (ESA) are studying how samples might be brought back to Earth from Mars safely. Backward planetary protection is key in this complex endeavour, as it is required to prevent potential adverse effects from returning materials to Earth's biosphere. As the question of whether or not life exists on Mars today or whether it ever did in the past is still unanswered, the effort to return samples from Mars is expected to be categoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 120 publications
0
30
0
Order By: Relevance
“…Planetary protection was established and needs to continue in effective implementation, to prevent space exploration causing this sort of pandemic scenario. A thorough assessment of various modes of inactivation and containment of martian sampling is ongoing (Craven et al, 2021).…”
Section: Planetary Protectionmentioning
confidence: 99%
“…Planetary protection was established and needs to continue in effective implementation, to prevent space exploration causing this sort of pandemic scenario. A thorough assessment of various modes of inactivation and containment of martian sampling is ongoing (Craven et al, 2021).…”
Section: Planetary Protectionmentioning
confidence: 99%
“…When determining chirality in organic compounds during life detection missions, contamination could arise from malfunctioning instrumentation [515], sampling [365], or terrestrial contamination [516]. Strategies employed for dealing with contamination include the use of sterilization procedures, e.g., decontamination heaters, UV radiation, chemical, and low-heat plasma ( [517] and references therein) and limiting the use of solvents and/or derivatization agents [500].…”
Section: Contamination Controlmentioning
confidence: 99%
“…More recently, conclusions from NASA's Sterilization Working Group (Craven et al, 2021), with input from sterilization experts across industry, government, and academia, indicated that terrestrial sterilization technologies should be extremely effective at inactivating all martian biology, because they likely share fundamental chemistries of chemical bonds. These proven modalities act by directly impacting chemical bonds in essential structures for life including nucleic acid, proteins, and lipid structures.…”
Section: -11)mentioning
confidence: 99%